MALEMAN TRADITION REVIVES THE NIGHT OF LAYLATUL QADR IN BILOK PETUNG VILLAGE - Hayadi Hayadi (STAI Darul Kamal NW Kembang Kerang, 2021)
This article will discuss “Maleman” tradition in Bilok Petung Village, Sembalun, East Lombok. “Maleman” tradition aims to liven up the night of Lailatul Qadar which is known as the night with a thousand glory in it. This article will explain how “Maleman” tradition is practiced based on religious texts and motivated by local custom and culture. Using the living hadis with stages of observation, interview, documentation, and interpretation, it can be concluded that; first, “Maleman” tradition is a practice based on normative arguments and historical reasons, second, the practice of “Maleman” is supported by the traditions inherent in the community, and third, “Maleman” tradition is a religious tradition and a form of harmonization between religion and cultural customs.